Alien versus Alien: The American mink, Neovison vison, as an indicator of invasive crayfish presence in the environment. (June 2022) - Yanuta, Grigorij; Klich, Daniel; Głogowski, Robert; Shilovich, Nikolai; Balcerak, Marek
Highlights: The mink's dietary composition showed great similarities across study sites. The basic diet consisted of rodents, amphibians, and fish. The presence of crayfish in the samples was dependent mostly on insects. The percentage of crayfish in scats was correlated with crayfish density. Crayfish density calculations based on mink's diets may differ during droughts. Abstract: Invasive animal species pose a significant threat to native biocenoses. For the management of invasive species, it is important to know their distribution. We aimed to investigate the potential use of American mink ( Neovison vison ) scats as a bioindicator of the presence and density of invasive crayfish Faxonius (Orconectes) limosus (Rafinesque, 1817) in the watercourses. The structure and seasonal dynamics of the mink's diet were studied in western Belarus. The dietary composition of the American mink showed great similarities across different types of watercourses (rivers and drainage channels). The basic diet consisted of rodents, amphibians, and fish. The crayfish's presence in the samples during the warm season was negatively dependent on all the other main prey groups, but mostly on aquatic insects. During the cold season the relations were weaker, and crayfish was negatively associated mostly with birds in the samples. The percentage of crayfish in scats collected during the warm season was correlated with crayfish density, which indicated that with higher crayfish densities, the mink more often used this type of prey. However, the regression model was only a moderate fit. Droppings collected during both seasons can indicate the presence of crayfish in the environment. We conclude that the American mink's diet can be a good indicator of invasive crayfish presence and their density in the environment. However, estimating crayfish density based on the mink's diet may deviate from the trend during years of low water level, therefore, it is necessary to first assess precipitation during the season.